2019
DOI: 10.3758/s13423-019-01655-0
|View full text |Cite
|
Sign up to set email alerts
|

Hunger increases delay discounting of food and non-food rewards

Abstract: How do our valuation systems change to homeostatically correct undesirable psychological or physiological states, such as those caused by hunger? There is evidence that hunger increases discounting for food rewards, biasing choices towards smaller but sooner food reward over larger but later reward. However, it is not understood how hunger modulates delay discounting for non-food items. We outline and quantitatively evaluate six possible models of how our valuation systems modulate discounting of various commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 54 publications
(61 reference statements)
3
30
2
Order By: Relevance
“…Sated individuals showed a different choice bias in each decision context, while hungry participants were risk-neutral across both decision contexts. Hunger has been previously associated with maladaptive behaviour (Bartholdy et al, 2016; Kirk and Logue, 1997; Skrynka and Vincent, 2019), however, the results in this study show that hunger makes people more “rational” in their behaviour. These individuals rely more on the objective expected value of an option, rather than the subjective expected utility (von Neumann and Morgenstern, 1944).…”
Section: Discussioncontrasting
confidence: 80%
“…Sated individuals showed a different choice bias in each decision context, while hungry participants were risk-neutral across both decision contexts. Hunger has been previously associated with maladaptive behaviour (Bartholdy et al, 2016; Kirk and Logue, 1997; Skrynka and Vincent, 2019), however, the results in this study show that hunger makes people more “rational” in their behaviour. These individuals rely more on the objective expected value of an option, rather than the subjective expected utility (von Neumann and Morgenstern, 1944).…”
Section: Discussioncontrasting
confidence: 80%
“…Fifth, is it unlikely that discount rates are the ultimate cause of behaviours influencing BMI and so we might need to reflect upon the possible causal direction of any association between discounting and BMI. For example, discount rates have been shown to change, both by an experimentally induced hunger manipulation (Skrynka & Vincent, 2019), and from an exercise intervention (Sofis, Carrillo, & Jarmolowicz, 2017). Evidence from a study in rats with diet-induced-obesity showed decreases in their discount rates (Robertson & Rasmussen, 2017), in line with other evidence (see studies discussed by Robertson & Rasmussen, 2017) that diet-induced obesity alters reward processing through the dopaminergic system.…”
Section: Ways Forwardmentioning
confidence: 68%
“…This does need to be born in mind however when we interpret the results in relation to discounting of food rewards. A speculative prediction based upon the link between hunger and discount rates (Lu, Zhou, Pan, & Zhao, 2019;Skrynka & Vincent, 2019) would be that discount rates may have been correlated to subjective hunger. This was effectively disproved however as we found evidence against a correlation between discounting (of money or food) and current state hunger, consistent with Rasmussen et al (2010).…”
Section: Discussionmentioning
confidence: 99%
“…The hunger related hormone ghrelin (Müller et al, 2015) increases impulsivity for food in rats (Anderberg et al, 2016) and humans (Cummings, Frayo, Marmonier, Aubert, & Chapelot, n.d.). In turn, hunger increases discount rates dramatically for food, and less so for other rewards (Skrynka & Vincent, 2019). Therefore before we can strongly rule out a relationship between discounting and BMI, we echo the call of Barlow, Reeves, McKee, Galea, and Stuckler (2016) to more fully understand the relationship of body composition and discounting of food rewards as compared to other commodities.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation